Kinesiology taping among other methods of edema therapy in patients treated for breast cancer - Urbanowicz, Lidia B. (Nursing Problems / Problemy Pielęgniarstwa, 2019)
Breast cancers (BC) are a serious oncological problem in Poland and throughout the world. Patients with BC are exposed to the appearance of lymphoedema. This is excessive accumulation of high-protein fluid in the interstitial space. This leads to an increase of the upper limb circuits on the tumour side, but also pain, muscle weakness, or limited mobility in the upper limb. They are several causes of oedema in patients with BC. It may be the removal of lymph nodes during surgery, scaring of the postoperative area, fibrosis of tissues, and damage to the lymphatic and blood vessels and lymph nodes after radiotherapy. Another cause may be the involvement of lymph nodes by the primary malignant tumour, tumour metastasis, or invasion of lymphatic vessels by the tumour. There are many physiotherapeutic methods (manual lymphatic drainage, kinesis-therapy, compression therapy) of prophylaxis and treatment of oedema. A method of supporting oedema therapy is kinesiology taping (KT). KT was developed by doctor Kenzo Kase in 1963. It involves sticking tape onto the skin. The result is improved flow of blood and lymph. Good conditions can be obtained for regeneration and reduction of oedema. It has an influence on reducing pain, on the regulation of muscle and fascia tension, increased or maintained range of motion, and reduction of skin tension. The aim of this article is to present the problems related with the occurrence of lymphoedema as a consequence of BC and propose the use of KT in oedema therapy by physiotherapists, nurses, and doctors.